Pre‐ and Intra‐Procedural Predictors of Reverse Remodeling After Cardiac Resynchronization Therapy: An MRI Study. (25th February 2013) - COCHET, HUBERT; DENIS, ARNAUD; PLOUX, SYLVAIN; LUMENS, JOOST; AMRAOUI, SANA; DERVAL, NICOLAS; SACHER, FREDERIC; REANT, PATRICIA; LAFITTE, STÉPHANE; JAIS, PIERRE; LAURENT, FRANÇOIS; RITTER, PHILIPPE; et al.
MRI Predictors of Reverse Remodeling After CRT: Introduction: Response rate after cardiac resynchronization therapy (CRT) remains suboptimal. We sought to identify pre‐ and intraprocedural predictors of response using MRI. Methods and Results: Sixty patients underwent MRI before CRT. Left ventricular (LV) volumes and ejection fraction were assessed on cine images. Intra‐LV dyssynchrony was defined as the maximal delay between first peaks of radial wall motion over 20 segments. Myocardial scar extent was quantified using delayed‐enhanced MRI. After CRT, the paced LV segment was characterized on preprocedural MRI with respect to presence of scar and mechanical delay, the latter being quantified using time to first peak of wall motion, expressed in percentage of the total LV activation. Echocardiography was performed before and 6 months after CRT to quantify reverse remodeling (RR). Mean RR at 6 months was 30 ± 29% of baseline LV end‐systolic volume. At univariate analysis, RR related to baseline LV end‐diastolic and end‐systolic volumes (R 2 = 0.101, P = 0.01; R 2 = 0.072, P = 0.04), intra‐LV mechanical dyssynchrony (R 2 = 0.351, P < 0.0001), scar extent (R 2 = 0.273, P < 0.0001), and presence of scar at pacing site (R 2 = 0.100, P = 0.01). QRS duration and mechanical delay at pacing site were not found related to RR (R 2 = 0.041, P = 0.12 and R 2 = 0.012, P = 0.4, respectively). At multivariate analysis intra‐LV mechanical dyssynchrony, scar extent, and LV end‐diastolic volume were independent predictors of RR (R 2 = 0.307, P = 0.001; R 2 = 0.096, P = 0.002, R 2 = 0.078, P = 0.005, respectively). Conclusion: Intra‐LV dyssynchrony and scar extent are independent predictors of RR after CRT. Scar at pacing site is associated to a lesser response to CRT. Mechanical delay at this site has no impact on the response.